Like, comment, subscribe : inside YouTube's chaotic rise to world domination - Bergen, Mark (Business journalist) (Viking, 2022)
"The definitive, deeply reported account of YouTube, the company that upended media, culture, industry, and democracy-by a leading tech journalist Across the world, people watch over a billion hours of video on YouTube every day. The sheer amount of video produced there is beyond comprehension. Every minute, over five hundred hours of footage are uploaded to the site, the equivalent of eighty-two years of video added a day. That anyone can easily access any minute of this footage-and the trillion minutes more already on YouTube-is a technical feat unmatched in the history of computing. Everyone knows YouTube. And yet virtually no one knows how it works. Like, Comment, Subscribe is the first book to explain exactly how YouTube's technology and business evolved, how it works, and how it helped Google grow to unimaginable power, a narrative told through the people who created YouTube and the Google engineers and chiefs who took it over. It's the story of an industry run amok, and of how corporate greed resulted in the unraveling of truth, the spread of violence, and the corruption of the internet, all for the sake of profit. Mark Bergen, the top Google reporter at Bloomberg Businessweek, might know Google better than any other reporter in Silicon Valley, having broken numerous stories about YouTube's and Google's business and scandals. His deep access within the companies makes Like, Comment, Subscribe a thrilling, character-driven story of technological and business ingenuity and the hubris that undermined it"--